Neurological Manifestations, Diagnostics, and Treatment of Giant Cell Arteritis: A Literature Review - Lukauskaitė, Ieva; Jatužis, Dalius; Valaikienė, Jurgita (Neurologijos seminarai, 2024)
Giant cell (temporal) arteritis is the most common primary systemic vasculitis. The main manifestation of this disease is new onset headache affecting people over 50 years old with an increased erythrocytes sedimentation rate (≥50mm/h). Other non-specific symptoms can include fever, loss of appetite, weight loss, fatigue, jaw pain and polymyalgia. The progression of the disease can lead to temporary or permanent monocular blindness due to retinal artery lesion and circulation problems. Later, the cerebral arteries can also be damaged, leading to stroke, more often in the posterior circulation.Painful, prominent, red temporal vessels with reduced pulses are observed in clinical examinations. A reliable and quick instrumental diagnostic method for giant cell arteritis is the extracranial color-coded duplex sonography. Typical sonographic findings in temporal arteritis are a ‘halo’ sign and increased blood flow velocities in the superficial temporal arteries. Other diagnostic methods include contrast-enhanced magnetic resonance imaging with angiography, positron emission tomography, and temporal artery biopsy.Once the diagnosis has been established, treatment with corticosteroids is initiated immediately, often with additional cytostatics (with the objective to reduce the risk of relapse), and biologic therapy with the interleukin 6 receptor antagonist Tocilizumab.If the treatment is started on time, the prognosis is good in the majority of cases. However, 1 in 3 patients experience a relapse episode in the first 2–3 years after the initial diagnosis. If the blindness has already occurred, it is usually irreversible. The treatment can prevent further complications, such as blindness in the unaffected eye and a reduction of the stroke risk.Clinical follow-up and extracranial color-coded duplex sonography are beneficial in observation of the disease progression, while allowing to make any required treatment corrections.Temporal arteritis is an insidious disease, usually starting with unspecific symptoms, such as fatigue and headache. Every patient older than 50 years old with a new onset headache and increased inflammatory markers should be carefully checked for temporal arteritis. If giant cell arteritis is diagnosed, the treatment must be started immediately in order to avoid blindness and stroke.